10. IDENTIFY OPPORTUNITIES AND TECHNIQUES TO REDUCE ACCESS BARRIERS TO TUBERCULOSIS CARE SERVICES IN VIETNAM (Vietnam Journal of Community Medicine, 2025)
Objective: The study aims to identify services within the tuberculosis care journey that can be decentralized, integrated, and people-centered. It seeks to select innovative initiatives, including digital health technologies and innovative initiatives, to facilitate these changes.Subject and methods: The study conducted in-depth interviews (n = 69), focus group discussions (FGDs) (n = 3), and workshops (n = 3) using a people-centered design approach. Participants included four key groups: individuals affected by tuberculosis; National Tuberculosis Program officials and healthcare workers at various levels; representatives from non-governmental and social support organizations; and representatives from the private healthcare sector.Results: The study identified and prioritized key areas requiring changes to improve tuberculosis care services. It compiled a list of innovative initiatives that could support improvements in these focus areas. Financial and social protection initiatives for tuberculosis care, along with communication solutions, were prioritized as essential activities to enhance tuberculosis care services in Vietnam.Conclusion: The study provided stakeholders’ perceptions about tuberculosis care in Vietnam, showing the importance of people-centered design in innovative initiative implementation in enhancing effectiveness and equality in care services delivery. Findings from the study aim to contribute to the improvement of tuberculosis care services, and support decision-making in the context of tuberculosis care in Vietnam.
Keywords: People-centered design; tuberculosis care; innovative health initiatives